ION EXTRACTION Na + , K + WITH LIGAND CALIXARENE pt- BUTYLCALIX [4 ] ETHYL ARENO TETRAETANOATO - Huamán P., Flora (2003)
Calixarenes are condensation products of phenols to substituted and formaldehyde in an alkaline medium 1. In this work, the extraction is carried out from an aqueous phase to an organic phase through the formation of complexes of sodium metal and potassium with the macrocyclic ligand calixarene p- tbutilcalix [4 ] arene tetraetanoato acetate ( L ) dissolved in chloroform the pH of 5, 7.5 and 8.5 . The absorbance of the alkali metal picrates ( - , K + Pi - , Na + Pi Pi - = 2,4,6 trinitrophenol ) was measured , and the complexes formed L M + , Pi -org organic phase at 310 nm . Experiments show that the extraction calixarene ( L ) ligand extracted at pH 7.5 to 72.3% sodium ion (I) in an aqueous solution of 2 to 20 ppm of concentration and extraction 35.6 % for potassium ion (I ) under the same conditions.